A randomised controlled trial of a consumer-focused e-health strategy for cardiovascular risk management in primary care: the Consumer Navigation of Electronic Cardiovascular Tools (CONNECT) study protocol. Issue 2 (31st January 2014) - Redfern, Julie; Usherwood, T; Harris, M F; Rodgers, A; Hayman, N; Panaretto, K; Chow, C; Lau, A Y S; Neubeck, L; Coorey, G; Hersch, F; Heeley, E; et al.
Abstract : Introduction: Fewer than half of all people at highest risk of a cardiovascular event are receiving and adhering to best practice recommendations to lower their risk. In this project, we examine the role of an e-health-assisted consumer-focused strategy as a means of overcoming these gaps between evidence and practice. Consumer Navigation of Electronic Cardiovascular Tools (CONNECT) aims to test whether a consumer-focused e-health strategy provided to Aboriginal and Torres Strait Islander and non-indigenous adults, recruited through primary care, at moderate-to-high risk of a cardiovascular disease event will improve risk factor control when compared with usual care. Methods and analysis: Randomised controlled trial of 2000 participants with an average of 18 months of follow-up to evaluate the effectiveness of an integrated consumer-directed e-health portal on cardiovascular risk compared with usual care in patients with cardiovascular disease or who are at moderate-to-high cardiovascular disease risk. The trial will be augmented by formal economic and process evaluations to assess acceptability, equity and cost-effectiveness of the intervention. The intervention group will participate in a consumer-directed e-health strategy for cardiovascular risk management. The programme is electronically integrated with the primary care provider's software and will include interactive smart phone and Internet platforms. The primary outcome is a composite endpoint of the proportion of people meeting the Australian guideline-recommended blood pressure (BP) and cholesterol targets. Secondary outcomes include change in mean BP and fasting cholesterol levels, proportion meeting BP and cholesterol targets separately, self-efficacy, health literacy, self-reported point prevalence abstinence in smoking, body mass index and waist circumference, self-reported physical activity and self-reported medication adherence. Ethics and dissemination: Primary ethics approval was received from the University of Sydney Human Research Ethics Committee and the Aboriginal Health and Medical Research Council. Results will be disseminated via the usual scientific forums including peer-reviewed publications and presentations at international conferences Clinical Trials registration number: ACTRN12613000715774.